2009
DOI: 10.2169/internalmedicine.48.2136
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Chronic Relapsing Tetanus Associated with Mandibular Osteomyelitis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The incubation period for tetanus is usually between 7 and 21 days in equids although incubation periods of as short as 1 day have been reported (Ribeiro et al, 2018) and incubation periods of as short as 36 h are common in humans (Vakil et al, 1964); therefore, both the first and second episode could be related to the recent shoeing. Given the absence of any detectable wounds at presentation, and the fact that the animal was clinically well and in work for the intervening 9 months, and that at second presentation there was a history of recent shoeing, it is perhaps most likely that this second episode of tetanus was indeed the result of a new and different insult, albeit also in the hoof, as is more common in the few reported cases of human recurrent or relapsing tetanus (Wakasaya et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The incubation period for tetanus is usually between 7 and 21 days in equids although incubation periods of as short as 1 day have been reported (Ribeiro et al, 2018) and incubation periods of as short as 36 h are common in humans (Vakil et al, 1964); therefore, both the first and second episode could be related to the recent shoeing. Given the absence of any detectable wounds at presentation, and the fact that the animal was clinically well and in work for the intervening 9 months, and that at second presentation there was a history of recent shoeing, it is perhaps most likely that this second episode of tetanus was indeed the result of a new and different insult, albeit also in the hoof, as is more common in the few reported cases of human recurrent or relapsing tetanus (Wakasaya et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Little or no active immunity develops as a result of clinical tetanus in people (Turner et al, 1957;Vakil et al, 1964), yet despite this, reports of relapsing or recurrent tetanus in people are very rare and non-existent amongst equids. In a review of the human literature, the first recurring case was reported by Whittemore et al in 1918 and this has been followed by other isolated single cases (Lemere et al, 1941;Vakil et al, 1964;Spenney et al, 1971;Bhatt et al, 1981;Lindley-Jones et al, 2004;Wakasaya et al, 2009 andAlhaji et al, 2011). In addition, three case series are described in the human literature (Garcia-Palmieri & Ramirez, 1957 reported on 5 cases; Patel et al 1961 on 17 cases andVakil et al, 1964 on 11 cases).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a case of malignant tumor-associated tetanus, in which three inoculations of toxoid failed to activate immunity, likely due to the effect of cancer-induced immunodeficiency, has been reported [27]. At present, these is no clear evidence on how many toxoid inoculations should be given to cancer-bearing patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, as tetanus is prone to recurrence, the acquisition of active immunity is essential to prevent recurrence after remission. Multiple doses of vaccination may be required to ensure adequate antibody titers and immunity to tetanus are achieved in cancer patients [17,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…However, surgical revision, notably the ablation of this defect, should have facilitated the recovery and decreased bacterial concentration. In the literature, 3 cases of relapsing C. tetani infections have been reported, but those patients had not received antitetanus vaccine and they did show signs of tetanus ( 4 , 5 ); 1 of these patients with mandible necrosis experienced relapse 8 months after discontinuation of metronidazole. …”
mentioning
confidence: 99%